Harmful Thoughts : Essays on Law, Self, and Morality - Dan-Cohen, Meir (Book collections on Project MUSE., 2002)
In these writings by one of our most creative legal philosophers, Meir Dan-Cohen explores the nature of the self and its response to legal commands and mounts a challenge to some prevailing tenets of legal theory and the neighboring moral, political, and economic thought. The result is an insider's critique of liberalism that extends contemporary liberalism's Kantian strand, combining it with postmodernist ideas about the contingent and socially constructed self to build a thoroughly original perspective on some of the most vital concerns of legal and moral theory. Dan-Cohen looks first at the.